Matrix Stiffness-Upregulated MicroRNA-17-5p Attenuates the Intervention Effects of Metformin on HCC Invasion and Metastasis by Targeting the PTEN/PI3K/Akt Pathway - Gao, Xiangyu; Qiao, Xiaona; Xing, Xiaoxia; Huang, Jinya; Qian, Jiali; Wang, Yi; Zhang, Yawen; Zhang, Xi; Li, Miao; Cui, Jiefeng; Yang, Yehong (Frontiers in Oncology, 2020)
Background: Metformin, a traditional first-line hypoglycemic agent for diabetes, recently exhibits better antitumor effect in hepatocellular carcinoma (HCC). However, its resistance and tolerance mechanism remain largely unexplored. Here we investigated whether high matrix stiffness attenuate the intervention effects of metformin on HCC invasion and metastasis, and explored its underlying molecular mechanism. Methods: FN-coated stiffness substrates with 6KPa, 10KPa and 16KPa, which simulated the stiffness of normal, fibrotic and cirrhotic livers, were established respectively for evaluation of matrix stiffness-mediated effects on HCC. Alterations in morphology, proliferation, motility and invasive/metastatic-associated genes (PTEN, MMP2, MMP9) of HCC cells grown on different stiffness substrates were comparatively analyzed before and after metformin intervention. Afterwards, the underlying molecular mechanism by which high matrix stiffness attenuates antitumor effect of metformin in HCC was further elucidated. Results: Metformin significantly inhibited proliferation, migration and invasion of HCC cells. Compared with the controls, HCC cells grown on higher stiffness substrate exhibited an obvious resistance to intervention effects of metformin on proliferation, invasion, and metastasis. High stiffness signals activated miR-17-5p/PTEN/PI3K/Akt signaling pathway in HCC cells via integrin β1 and in turn resulted in MMP2 and MMP9 upregulation. Simultaneously, integrin β1 knockdown or PI3K inhibitor partially reversed the activation of the above signaling molecules. On the other hand, metformin also remarkably upregulated PTEN expression in HCC cells grown on same stiffness substrate, and suppressed the activation of PI3K/Akt/MMPs pathway but no effect on integrin β1 expression. More importantly, the increase degree of PTEN expression and decrease degrees of Akt phosphorylation level and MMP2, MMP9 expressions in HCC cells on 16KPa stiffness substrate were evidently weakened after metformin intervention compared with the controls on 6KPa stiffness substrate. Conclusions: Increased matrix stiffness significantly attenuates the inhibitory effect of metformin on HCC invasion and metastasis, and a common pathway of PTEN/PI3K/Akt/MMPs activated by mechanical stiffness signal and inactivated by metformin contributes to matrix stiffness-caused metformin